Hearing analysis in heterozygous and homozygous klotho gene deficient mice - Na Yuan (Journal of Otology, 2018)
Objective: To understand the crucial role of the klotho gene in hearing development in mouse models. Methods: PCR was used to identify CBA mice with different genotypes, i.e. WT, heterozygous (klotho +/−) or homozygous (klotho −/−). Mice phenotype and weight were recorded postnatal 25 days (P-25) and auditory brainstem responses (ABR) were used to determine auditory function at P-60. Results: klotho −/− mice tended to have smaller size, lighter weight and higher ABR thresholds at P-60, showing early onset age-related hearing loss (ARHL). Conclusion: Heterozygous and homozygous klotho deficient mice exhibit different degrees of hearing loss at young age, with homozygous mice (klotho −/−) showing more severe hearing loss. Our results indicate that persisted expression of klotho protein in the inner ear may potentially delay the onset of ARHL and play an important role in the protection of auditory function. Keywords: Homozygous, Klotho gene, Inner ear, Hearing loss